Rancang Bangun Sistem Informasi Manajemen Laporan Keuangan Dengan Menggunakan Metode Rapid Application Development (RAD) - Pratiwi, Mega Retno; Perwitasari, Ika Devi (STMIK Budi Darma, 2024)
This study aims to design and build a web-based financial report management information system at PT Sapta Alamku Jaya to improve efficiency and effectiveness in managing financial reports. Currently, the company still uses Microsoft Excel, which causes problems in the reporting process and data storage, so inefficiencies often occur. To overcome this, the proposed system uses the Rapid Application Development (RAD) method, which allows rapid system development with an iterative approach. The system uses PHP Framework for web development and MySQL as the database. The results showed that the developed system could facilitate the admin in managing financial data and improve the accuracy and speed of the reporting process.